2019
DOI: 10.1038/s41586-019-1152-0
|View full text |Cite
|
Sign up to set email alerts
|

A rapidly changing jet orientation in the stellar-mass black-hole system V404 Cygni

Abstract: Powerful relativistic jets are one of the main ways in which accreting black holes provide kinetic feedback to their surroundings. Jets launched from or redirected by the accretion flow that powers them should be affected by the dynamics of the flow, which in accreting stellarmass black holes has shown increasing evidence for precession 1 due to frame dragging effects that occur when the black hole spin axis is misaligned with the orbital plane of its companion star 2 . Recently, theoretical simulations have s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(114 citation statements)
references
References 51 publications
5
107
2
Order By: Relevance
“…Given that the inclination of the inner accretion disk of J1858 appears to be low, this explanation appears less likely to be applicable to J1858. However, misalignments of ∼ 15 • between the orbit of the system and the inner accretion disk have been observed in Cygnus X-1 (see e.g., Tomsick et al 2014;Walton et al 2016) and even larger misalignments (possibly ∼ 30 • − 50 • ) have been observed in the two systems V4641 Sgr and V404 Cyg (Maccarone 2002;Miller-Jones et al 2019), which are very similar to J1858. Thus, the possibility of a large misalignment between the inclination of the orbit and inner accretion disk, leading to the obscuration of the inner regions of the accretion disk by a flared disk, cannot be entirely ruled out.…”
Section: Comparison With Similar Systemsmentioning
confidence: 98%
“…Given that the inclination of the inner accretion disk of J1858 appears to be low, this explanation appears less likely to be applicable to J1858. However, misalignments of ∼ 15 • between the orbit of the system and the inner accretion disk have been observed in Cygnus X-1 (see e.g., Tomsick et al 2014;Walton et al 2016) and even larger misalignments (possibly ∼ 30 • − 50 • ) have been observed in the two systems V4641 Sgr and V404 Cyg (Maccarone 2002;Miller-Jones et al 2019), which are very similar to J1858. Thus, the possibility of a large misalignment between the inclination of the orbit and inner accretion disk, leading to the obscuration of the inner regions of the accretion disk by a flared disk, cannot be entirely ruled out.…”
Section: Comparison With Similar Systemsmentioning
confidence: 98%
“…Here, precession and disc rotation are both anti-clockwise. Adapted from an animation made by ICRAR in association with [144] (the original movie can be found at https: //vimeo.com/332582739).…”
Section: The Relativistic Precession Modelmentioning
confidence: 99%
“…Perhaps the most spectacular evidence of misalignment is the recent result of Miller-Jones et al [144], who used very long baseline interferometry to discover that the jets of V404 Cygni are precessing. The half opening angle of the precession cone is ∼ 18 • , and the precession period is in the range ∼ 1 second to 2.6 hours (the pattern of sampling makes it difficult to estimate the precession period, or even to conclusively confirm that that the changes in jet orientation are periodic).…”
Section: Are These Systems Misaligned?mentioning
confidence: 99%
“…Moreover, there is increasing evidence that at least in some sources the inner disk is precessing (see for eg. Ogilvie & Dubus 2001;Liska et al 2018;Motta et al 2018b;Miller-Jones et al 2019) and perhaps that causes (some of) the discrepancy between inclinations measured through X-ray reflection models. On the other hand, the discrepancy in inclinations estimated from optical measurements is usually only a few degrees (Kreidberg et al 2012).…”
Section: Methods Of Deciding Inclination Constraintsmentioning
confidence: 99%